Doing sensory ethnography - Pink, Sarah (Sage Publications, 2015)
"Drawing on an explosion of new, cutting edge research Sarah Pink uses real world examples to bring this innovative area of study to life. She encourages us to challenge, revise and rethink core components of ethnography including interviews, participant observation and doing research in a digital world. The book provides an important framework for thinking about sensory ethnography which stresses the numerous ways that smell, taste, touch and vision can be interconnected and interrelated within research. Bursting with practical advice on how to effectively conduct and share sensory ethnography this is an important, original book."--Page 4 of cover.